A framework for business cloud services (BCSS) in SMEs - Alsafi, Tariq (Cranfield University, 2022)
The Saudi economy is changing rapidly to move from depending on energy to one with a wide range of indigenous businesses. Successful Small and Medium Enterprises (SMEs) are important in this economic transformation. Many Saudi Arabia SMEs are adopting Cloud Based Enterprise IT Services as the option to grow and sustain due to its cost and agility. However, they are often confused by the large international Cloud Services suppliers and not all SME reap the right business value from their Cloud Services investments. This research aims to create an approach to assist Saudi SMEs based on a strong research understanding. A novel framework is created that takes into account of the different functions of different Business Cloud Services, the different business requirements of each SME and their existing capabilities and readiness. Rather than treating all Cloud Services as the same, the researcher differentiates into three types: Digitalisation, Packaged and Enterprise. The research relates the Technological Resources, Organisation Capabilities, Organisational Requirements and Business Benefits for each of the Cloud Service types and then integrate them into one cohesive framework. This research adopted a pragmatic paradigm. The conceptual framework is developed through literature, contextualised, and improved qualitatively through interviews with 17 experts and 54 practitioners. The model was quantitatively examined with 395 questionnaires. The framework was developed into a readiness assessment tool and validated with three Saudi SMEs, who value the approach as beneficial business advice. The framework contributes to the improved structural knowledge of Cloud Services adoption. The constructs add contextualised factors to understand the business considerations relevant to Saudi SMEs.
McLaughlin, Patrick - Associate Supervisor
Keywords: Business Cloud Services; SMEs; Saudi Arabia; Capabilities; Transformation Requirements; business requirements